2018
DOI: 10.1002/hed.25414
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities and human papillomavirus status in oropharyngeal cancer: A systematic review and meta‐analysis

Abstract: Background: This study used a meta-analysis to quantify the degree to which the racial disparity in overall survival for black versus white Americans with oropharyngeal squamous cell carcinoma (OPSCC) persists after adjusting for human papillomavirus (HPV) status. Methods: PubMed/MEDLINE, Cochrane Database of Systematic Reviews, and CINAHLA were searched through November 2017. The PRISMA statement was followed. The pooled hazard ratio (HR) was calculated using a random-effects model. Results: Five studies met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Similar to previous larger studies and published metanalysis focused on racial disparities in HNC [8,9,64,65], our pilot study results support that Black and White HNC patients differ significantly in terms of highest educational obtainment and annual income level. Exposure to other known HNC risk factors appeared similar between Whites and Blacks, including alcohol use and current smoking status.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous larger studies and published metanalysis focused on racial disparities in HNC [8,9,64,65], our pilot study results support that Black and White HNC patients differ significantly in terms of highest educational obtainment and annual income level. Exposure to other known HNC risk factors appeared similar between Whites and Blacks, including alcohol use and current smoking status.…”
Section: Discussionsupporting
confidence: 90%
“…We recently conducted a meta‐analysis in which we concluded that HPV accounts for much of the observed racial disparity in survival for OPSCC 14 . However, this conclusion was reached without directly measuring racial disparities by HPV status, but rather by adjusting for HPV status in the overall model.…”
Section: Introductionmentioning
confidence: 99%
“…HPV-related oropharyngeal cancer has a lower incidence in Black Americans and may have a significant impact on the survival differences. 6,12,55 Finally, the SEER registry does not have accurate tobacco use data, although prior studies that have stratified patients by smoking habits showed no impact on disparaties. 10,11,24…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4] Oropharyngeal and oral cavity cancers have similar incidence rates across cohorts, although the prevalence of HPV, a significant positive prognostic factor, is much lower in Black individuals. 5,6 Despite ongoing advancements in surgery, radiation therapy (RT), and chemotherapy, survival in HNC remains poor, particularly among Black patients. 7 Multiple studies examining racial/ethnic disparities have found worse outcomes in Black NH patients than in White NH patients, although there has not been a comparison with Hispanic patients.…”
Section: Introductionmentioning
confidence: 99%